PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP PENCAPAIAN TARGET PENJUALAN PSM (PRODUK SPESIAL MINGGUAN) - STUDI KASUS: ALFAMART FRANCHISE CABANG CIBOGO - Nurmala, Padila (PT Naureen Digital Education, 2024)
The purpose of this research is to determine the influence of work motivation and work culture on achieving PSM (Weekly Special Products) sales targets. The population in this study were 4 employees of the Alfamart Franchise Shop, Cibogo Branch, Ciranjang. The sample used is representative of each division. The data collection method used is the interview method. Based on the research results, it was concluded that based on the respondents' answers, work culture is a shared responsibility, prioritizing good support between employees has become a work culture that has been maintained for a long time. This can also be concluded that apart from sustainable motivation, an optimal work culture also has a significant influence on achieving PSM (Weekly Special Products) sales targets at the Alfamart Franchise Store, Cibogo Branch, Ciranjang